Application of Fuzzy Logic in Land Consolidation-Classification Studies - Ertunç, Ela; Çay, Tayfun (Prof. Dr. Ismail SARITAS, 2016)
Land classification is one of the most important stages of consolidation projects. The success and timely completion of this project depends on that this classification is useful and fair and are accepted by landowners. Different methods have been developed for the classification. Effects on the success of the land consolidation of the results of these methods are being investigated. In this study, fuzzy logic method has been used for land classification according to Law No. 5403. In Mamdani Type Fuzzy Logic, Values of soil index, productivity index and the location index, which are used to determine the value of the parcel index, have been defined as input, whereasÃ‚Â the value of parcel index have been defined as the output. Inputs and outputs have been converted to the linguistic terms (such as very efficient, inefficient, somewhat efficient, remote, near) by creating membership functions. Rule base has been created for calculating of the parcel index. As a result of fuzzy inference and defuzzification process, the model formed by Mamdani Type Fuzzy Logic gives the value of parcel index. By giving random input values to test generated model, results has been compared with results obtained manually.Ã‚Â